29th Joint Propulsion Conference and Exhibit 1993
DOI: 10.2514/6.1993-2555
|View full text |Cite
|
Sign up to set email alerts
|

Navier-Stokes analysis of radial turbine rotor performance

Abstract: ABSTRACTspecific fuel consumption requirements have been reported by Snyder and Roelke [1]. An analysis of flow through a radial turbine rotor using the three-dimensional, thinlayer Navier-Stokes code RVC3D is described. The rotor is a solid version of an air-cooled metallic radial turbine having thick trailing edges, shroud clearance, and scalloped-backface clearance. Results are presented at the nominal operating condition using both a zero-clearance model and a model simulating the effects of the shroud and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the present study, the supercritical air is employed to reduce site area and increase the energy density of CAES system, 16 so the compressed air in the multistage radial turbine expands from supercritical to atmospheric conditions to obtain higher output power, which differs from the ordinary operating condition of radial turbines (Figure 1). [16][17][18][19][20][21][22][23] In addition, radial turbines, which are shrouded and unshrouded rotors with different blade profile, are all included in the multistage radial inflow turbine to meet the requirement of operation condition, thus it is difficult for the engineers to determine the stage that has higher flow loss to conduct performance improvement. Although some studies 24 has been conducted on the aerodynamic performance and internal flow patterns of multistage radial inflow turbine, the effects of supercritical condition and geometric parameters on the aerodynamic performance and flow characteristic of multistage radial turbine in CAES system is also still not revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the supercritical air is employed to reduce site area and increase the energy density of CAES system, 16 so the compressed air in the multistage radial turbine expands from supercritical to atmospheric conditions to obtain higher output power, which differs from the ordinary operating condition of radial turbines (Figure 1). [16][17][18][19][20][21][22][23] In addition, radial turbines, which are shrouded and unshrouded rotors with different blade profile, are all included in the multistage radial inflow turbine to meet the requirement of operation condition, thus it is difficult for the engineers to determine the stage that has higher flow loss to conduct performance improvement. Although some studies 24 has been conducted on the aerodynamic performance and internal flow patterns of multistage radial inflow turbine, the effects of supercritical condition and geometric parameters on the aerodynamic performance and flow characteristic of multistage radial turbine in CAES system is also still not revealed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was also drawn by Tirres 8 when he predicted the performance of the solid version of a cooled radial rotor, and it was shown that the backface clearance loss for the rotor accounted for 79% of the total clearance losses. Larosiliere 9 simulated the backface clearance flow in a deeply scalloped radial turbine. The author presented entropy contours and velocity vectors at different quasi-normal planes, and showed the backface clearance leakage vortex.…”
Section: Introductionmentioning
confidence: 99%